Educational System for Control Development: Furuta Pendulum– Automatic Control (2012)
This paper present the description and the dynamic of the Rotational Inverted Pendulum or Furuta Pendulum, educational platform for demonstration and development of control laws, in order to have reference material for those interested in perform implementations with the existing platform in the Electronic Engineering laboratory-Sogamoso.